Development of a supplier selection risk management framework for Iranian automotive industry - Kamran, Mohtasham (2016)
Supply chain management (SCM) is the process of managing information, materials,and finances in the whole chain of manufacturing from part suppliers to main manufacturer to wholesalers, market and consumers. SCM is an attempt to coordinate and integrate the processes above amongst companies. Supply chain management focuses on the efficiency and cost-effectiveness of activities across the whole system; the entire system costs from goods transportation, distribution and inventories of parts and raw materials, ongoing works, etc. has to be minimized. Therefore, it is not a plain managerial activity to lower the cost of transportation and inventory, but it is rather a system-wide approach to supply chain management. Disruption of the supply chain can happen at any level of the process; therefore,investigation on the possible risks in the supply chain is inevitable in any SCM activity. Due to the increase in outsourcing production strategy, which has extended the supply chain elements and complexity, supply chain disruption risk has increased exponentially and risk management policies are supposed to be developed according to this type of risk. Supplier failure is one of the largest uncertainty sources in the SCM since approximately 70%-80% of the risks are attributed to the vendors failure in the Supply Chain. For instance, unstable financial situation of a supplier can directly affect the supply chain of an enterprise and cause considerable damage and cost. Therefore, supplier selection importance has come to the forefront of supply chain risk management and has attracted to establish a sound and flawless supplier selection process.Since supplier failure is a major threat to the supply chain and ensuring proper supplier selection is crucial, this study aimed to establish a supplier selection procedure that can reduce the risk in supply chain. Linear weighting method is used to analyze the risk factors and construct an empirically reliable model for supplier evaluation.A total number of 200 questionnaires were distributed amongst the automobile companies of Iran, Iran Khodro, Kerman Motor, Zagross Khodro. Questionnaire respondents are managers, engineers, and decision makers who are involved in supplier selection process. The analysis of industry responses was completed using SPSS software. The conceptual model development purpose is to define the way that research hypothesis is designed. Pearson correlation test is applied to the data obtained through questionnaire distribution. A multiple linear regression model was employed to build a systematic supplier selection model. In the proposed multicriteria supplier selection model, product quality had the highest degree of influence on supplier selection risk management. Human resource of supplier is the second influential risk factor that can cause disruption in supply chain. It was found that in a sequential order, product quality(22.3%), human resources(19.9%), financial power(17.1%), governmental support(14.5%), IT and R&D opportunities(13.4%),and environmental(12.8%) vulnerability of the supplier are critical to supply chain management while their degree of influence decreases respectively.The outcome of the research is a framework that explains the proposed supplier selection model, which is obtained and designed based on combination of conceptual model and vendor selection model. After all, the proposed framework received positive responses from the manufacturer companies supporting its applicability andusefulness. It is claimed that the proposed supplier selection framework can reduce the supplier-induced risks to the supply chain.